Linear delay differential equation in a dynamical system and its application mixing problem - 304864 Chu, Hui Yi (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Sains (Matematik Industri)) - Universiti Teknologi Malaysia, 2006